Visual function and visual ability in adolescents with oculocutaneous albinism. (May 2022) - Naipal, Shivani; Rampersad, Nishanee
Individuals with ocular and oculocutaneous albinism (OCA) have significantly reduced visual acuity (VA) resulting in visual impairment (VI). The aim is to report on the visual function of adolescents with OCA and their quality of life (QoL) in terms of their visual ability. A total of 28 adolescents with OCA participated in this study. Tests of visual function included distance VA, refractive error, contrast sensitivity (CS), and colour vision. The Cardiff Visual Ability Questionnaire for Children (CVAQC) was used to assess visual ability. All participants presented with cutaneous hypopigmentation and nystagmus, while only two had strabismus. A mean myopic refractive error was found, and with-the-rule (WTR) astigmatism was most common. The mean best-corrected VA was 0.81 ± 0.17 logMAR and 0.81 ± 0.18 logMAR in the right and left eyes, respectively. The mean CS with the best refractive correction was 1.23 ± 0.33 log CS in the right eye and 1.29 ± 0.33 log CS in the left eye. The mean Cardiff visual ability score was −0.37 ± 0.79 log units. The variation of refractive errors and the magnitude thereof underscores the need for regular eye examinations in individuals with OCA. The majority of participants had moderate VI, and these participants had a better mean Cardiff visual ability score than those with severe VI. Similarly, participants with normal binocular CS had a better Cardiff visual ability score than those with a loss of CS.